Studi etnobotani tumbuhan obat Suku Anak Dalam di Desa Sungai Jernih Kecamatan Rupit Kabupaten Musi Rawas Utara Sumatera Selatan - Laila Sri Pujihastuti; Nina Tanzerina; Nita Aminasih (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
The use of plants as traditional medicine has been widely known for a long time by the community, especially the Anak Dalam Tribe in Sungai Jernih Village, Rupit District Musi Rawas Utara Regency, South Sumatera. The purpose of this research is to inventoryof the types of medicinal plants, knowing family and habitus, types of diseases, plant organs used, processing methods and how to use plants used by the community as traditional medicine to treat various types of diseases. Method which conducted using a descriptive survey method by conducting interviews from three speakers who are traditional healers to help the process of collecting data in the field. The results showed that plants that were used as medicine by tribal children were found as many as 93 types of plants with 48 families and the largest families were Fabaceae and Piperaceae (6.45%) and were able to treat as many as 47 types of diseases with 116 medicinal ingredients. The largest plant habitats are shrubs, (32.25%) and as much as (60.21%) medicinal plants that’s grow wild both that grow wild in the forest and grow wild in the yard of the house. The most part of the plant organs used was the leaves (59.13%), the largest method of processing was boiling (67.74%) and the largest way of using it was drinking (61.29%%).